A measure of tourist experience quality: the case of inland tourism in Malaga. - Soler-García, Ismael Pablo; Gemar-Castillo, Germán (Taylor & Francis, 2017)
Although Malaga is a major tourist destination, research focused on the coastal area. However, the interior of the province has a growing tourism industry, so this tourism industry needs to be studied. The goal of this study was to analyse the attractiveness of this destination through the perceived quality of tourists’ experiences, measuring the effect of each agent involved in tourists’ overall assessment of the destination. Using a two-step factorial analysis of data gathered with 660 valid questionnaires collected through an on-the-ground survey, the composition structure and relationships of satisfaction factors in the destination were identified. Subsequently, the relationships between each agent with tourists’ overall assessment of the destination were extracted. The results suggest that tourism businesses are primarily responsible for the final quality of this destination, followed by organisations responsible of the management of tourism resources. Further, the results also show that there is room for improvement in quality. The worst ratings were given for the quality of leisure facilities and restaurants, while the aspects most valued by users have a low capacity for differentiation (i.e. climate, courtesy and value for money). Therefore, this tourist destination would benefit from implementing a system of integrated quality management.
Keywords: Málaga (Provincia) - Descripción y viajes; Turismo - Calidad; Tourist destination; Quality of service; Quality of tourist destination; Measurement of service quality